2005
DOI: 10.1117/1.1922147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hemoglobin concentration variation on the accuracy and precision of glucose analysis using tissue modulated, noninvasive, in vivo Raman spectroscopy of human blood: a small clinical study

Abstract: Tissue modulated Raman spectroscopy was used noninvasively to measure blood glucose concentration in people with type I and type II diabetes with HemoCue fingerstick measurements being used as reference. Including all of the 49 measurements, a Clarke error grid analysis of the noninvasive measurements showed that 72% were A range, i.e., clinically accurate, 20% were B range, i.e., clinically benign, with the remaining 8% of measurements being essentially erroneous, i.e., C, D, or E range. Rejection of 11 outli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 15 publications
1
51
0
1
Order By: Relevance
“…225,226 It was later shown that this approach was highly sensitive to an individual's peripheral microcirculation 227,228 and the test subject's hemoglobin concentration. 229 Much of the early work on the in vivo analysis of hemoglobin oxygenation for surgical applications was carried out by Torres Filho et al They reported the utility of UV-RRS for the simultaneous identifications of oxyhemoglobin and deoxyhemoglobin in the microvessels of a living rat using a single excitation wavelength (406.5 nm in one study, 230 and 532 nm in another 231 ). When the rat's hemoglobin saturation (as measured by a commercial oximeter) was <1% (deoxygenated) or >98% (oxygenated), a single Raman peak was observed.…”
Section: In Vivo Raman Spectroscopic Analysis Of Bloodmentioning
confidence: 99%
“…225,226 It was later shown that this approach was highly sensitive to an individual's peripheral microcirculation 227,228 and the test subject's hemoglobin concentration. 229 Much of the early work on the in vivo analysis of hemoglobin oxygenation for surgical applications was carried out by Torres Filho et al They reported the utility of UV-RRS for the simultaneous identifications of oxyhemoglobin and deoxyhemoglobin in the microvessels of a living rat using a single excitation wavelength (406.5 nm in one study, 230 and 532 nm in another 231 ). When the rat's hemoglobin saturation (as measured by a commercial oximeter) was <1% (deoxygenated) or >98% (oxygenated), a single Raman peak was observed.…”
Section: In Vivo Raman Spectroscopic Analysis Of Bloodmentioning
confidence: 99%
“…In a recent report, 24 the difference spectrum between pressed and unpressed phases was interpreted as the whole blood spectrum. Each spectrum was obtained with excitation power ~31 mW and integration time ~100 seconds.…”
Section: Tissue Modulation Approachmentioning
confidence: 99%
“…17 With the advent of high quantum efficiency CCD detectors and holographic diffractive optical elements, researchers have increasingly employed CCD-based dispersive spectrometers. 3,[18][19][20][21][22][23][24] The advantages of dispersive NIR Raman spectroscopy are that compact solid-state diode lasers can be used for excitation, the imaging spectrograph can be f-number matched with optical fibers for better throughput, and cooled CCD detectors offer shot-noise limited detection.…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel optical measurement [1][2][3][4] and imaging [5][6][7][8][9] methods for biomedicine require preclinical optimization and calibration. Such calibration is performed on standardized phantoms -simpli¯ed physical models of tissues.…”
Section: Introductionmentioning
confidence: 99%